Integrasi Keilmuan sebagai Solusi Dikotomi: Menuju Pendidikan Islam yang Kokoh dan Kompetitif - Elisah Novi Latifah; Saefrudin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
This article examines the issue of knowledge dichotomy in Indonesian Islamic education, which has persisted for centuries and become the root cause of various intellectual and moral crises among Muslim generations. The dichotomy between religious sciences and general sciences is not an original legacy of classical Islamic civilization, but rather a product of colonialism that systematically separated knowledge domains. Through library research with descriptive qualitative analysis, this study traces the historical roots of such dichotomy, analyzes the concept of knowledge integration proposed by contemporary Muslim thinkers such as Ismail Raji al Faruqi, M. Amin Abdullah, and Kuntowijoyo, and identifies implementation models at Islamic educational institutions in Indonesia. The findings indicate that knowledge integration has multidimensional implications, encompassing epistemological strengthening, pedagogical transformation, character building, and enhanced institutional relevance. Successful implementation requires synergy between curriculum renewal, educator competency development, policy support, and sustainable infrastructure investment.